2020
DOI: 10.1007/978-3-030-58112-1_17
|View full text |Cite
|
Sign up to set email alerts
|

Parallelized Bayesian Optimization for Expensive Robot Controller Evolution

Abstract: An important class of black-box optimization problems relies on using simulations to assess the quality of a given candidate solution.Solving such problems can be computationally expensive because each simulation is very time-consuming. We present an approach to mitigate this problem by distinguishing two factors of computational cost: the number of trials and the time needed to execute the trials. Our approach tries to keep down the number of trials by using Bayesian optimization (BO) -known to be sample effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…While it is only rarely able to compete in a scenario with a batch size of two, it can compete on a total of ten function/dimension combinations with a batch size of 16. This coincides with other experiments that have shown that a CMAES starts outperforming modelbased methods when it is given enough budget [30]. This observation is further signified considering Figure 6.…”
Section: A Static Batch Size Experimentssupporting
confidence: 90%
“…While it is only rarely able to compete in a scenario with a batch size of two, it can compete on a total of ten function/dimension combinations with a batch size of 16. This coincides with other experiments that have shown that a CMAES starts outperforming modelbased methods when it is given enough budget [30]. This observation is further signified considering Figure 6.…”
Section: A Static Batch Size Experimentssupporting
confidence: 90%
“…Rebolledo et al [30] showed that parallelization can also be used in situations where the best choice of kernel, model, or infill criteria is unknown. A number of samples can be generated by building multiple differently configured models and optimizing them with different infill criteria in parallel.…”
Section: A Related Literaturementioning
confidence: 99%